2018
DOI: 10.1117/1.jrs.12.026019
|View full text |Cite
|
Sign up to set email alerts
|

Crop classification from Sentinel-2-derived vegetation indices using ensemble learning

Abstract: The identification and mapping of crops are important for estimating potential harvest as well as for agricultural field management. Optical remote sensing is one of the most attractive options because it offers vegetation indices and some data have been distributed free of charge. Especially, Sentinel-2A, which is equipped with a multispectral sensor (MSI) with blue, green, red and near-infrared-1 bands at 10 m; red edge 1 to 3, nearinfrared-2 and shortwave infrared 1 and 2 at 20 m; and 3 atmospheric bands (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 79 publications
1
77
0
1
Order By: Relevance
“…Sentinel-2 carries a MultiSpectral Instrument (MSI) with 13 bands in the visible, near infrared, and shortwave infrared part of the spectrum. These state-of-the-art specifications have been used in recent research on crop classification [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel-2 carries a MultiSpectral Instrument (MSI) with 13 bands in the visible, near infrared, and shortwave infrared part of the spectrum. These state-of-the-art specifications have been used in recent research on crop classification [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Qiu et al[2] mapped winter wheat in North China using MODIS data, and reported a producer accuracy of 82.77% and a user accuracy of 81.49% when compared to the classification results from Landsat images. Landsat and Sentinel images are data sources which are often used in agricultural remote sensing [25][26][27][28]. However, Landsat or Sentinel images have generally been used at smaller scales in previous research, because of the difficulties in image pre-processing [29,30].…”
mentioning
confidence: 99%
“…On invaded landscapes, Parthenium weed expands more rapidly than native plants [60]. Spectral bands alone are not enough to achieve reliable mapping accuracies [61]. Increasing data dimensionality by combining, among others, Sentinel-2 image bands, vegetation indices and other variable types and applying an appropriate feature selection approach, higher Pathenium mapping accuracy can be achieved.…”
Section: Implications Of Findings In Parthenium Weed Managementmentioning
confidence: 99%